Neurocognitive Disorder and Emotional Symptoms in HIV+ Brazilian Elderly: Influence of Gender, Income, Diet, and Sleep - Barroso, Sabrina Martins; Sousa, Kelly Cristina Ramira (Frontiers in Human Neuroscience, 2021)
The purpose of this study was to identify factors associated with HIV-associated neurocognitive disorder (HAND) and symptoms of anxiety and depression in HIV+ Brazilian elderly on antiretroviral treatments. The study included 112 HIV+ elderly who completed a questionnaire, tests for cognitive screening, attention, problem solving, processing speed, visual perception, memory, and anxiety and depression scales. The results showed presence of HAND (89.3%), pathological anxiety (48.2%) and depression (58%) in the sample. Higher income was a protective factor for HAND (OR = 0.33). Waking up well-rested (OR = 0.63) and better diet quality (OR = 0.62) reduced the chance of pathological anxiety. Higher education (OR = 0.74) and waking up well-rested (OR = 0.61) reduced the chance of depression. Being female (OR = 7.73) increased the chance of depression. It can be concluded that it is important to evaluate cognitive and emotional aspects of HIV+ elders and to consider social and educational status, diet, and sleep in interventions, paying special attention to elderly women.